2023
DOI: 10.1186/s12913-023-09519-z
|View full text |Cite
|
Sign up to set email alerts
|

Living with type 1 diabetes in Neno, Malawi: a qualitative study of self-management and experiences in care

Abstract: Background The prevalence of type 1 diabetes (T1D) is increasing in low-income countries including Malawi. In this setting, care is frequently impacted by challenges in diagnosis and management. Access to high-quality T1D care remains limited in Malawi, with fairly low availability and high cost of insulin and other supplies and diagnostics, lack of T1D knowledge, and absence of readily accessible guidelines. In the Neno district, Partners In Health established advanced care clinics at district… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“… 4 5 PEN-Plus strategies have since been initiated in Haiti, Malawi and Liberia. Research has shown PEN-Plus to be affordable, 4 effective, 6 acceptable 7 8 and scalable, 5 but questions still remain about how to implement in new settings and how to scale up. PEN-Plus was identified by the Lancet Commission on Reframing NCDs and Injuries for the Poorest Billion (NCDI Poverty Commission) as a promising example of care through integrated teams.…”
Section: Introductionmentioning
confidence: 99%
“… 4 5 PEN-Plus strategies have since been initiated in Haiti, Malawi and Liberia. Research has shown PEN-Plus to be affordable, 4 effective, 6 acceptable 7 8 and scalable, 5 but questions still remain about how to implement in new settings and how to scale up. PEN-Plus was identified by the Lancet Commission on Reframing NCDs and Injuries for the Poorest Billion (NCDI Poverty Commission) as a promising example of care through integrated teams.…”
Section: Introductionmentioning
confidence: 99%